Program Pengadaan Alat Berat Pada CV PG Dengan Metode Protoyping (Life Cycle Using Prototyping) - Yusup Indra Wijaya (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
PG were still using a manual system, especially the administration section which is handling information process that was not regulated in a good information base system, namely data processing.Procurement of heavy equipment which takes quite a long time from manual recording, preparation of reports, to searching for meaningful data on the company's heavy equipment, and can also assist the administration in searching for information contained in the procurement of heavy equipment. To overcome this problem, a program was created that could assist administration staff in managing data on heavy equipment procurement, speed up data collection on heavy equipment procurement, make it easier for administration to store data, assist in knowing financial income and expenditure transactions, help speed up data search and creation, reports and others. With the protoyping model (life cycle using prototyping) for the programming languages ​​used are PHP and MySQL. The result is to make it easier for CV. PG in the process of procuring heavy equipment data, and can also help the administration in searching for data that is in the procurement of heavy equipment.